Greenhouse gases and performance of growing pigs fed wheat-based diets containing wheat millrun and a multi-carbohydrase enzyme. (29th September 2021) - Kpogo, Agbee L; Jose, Jismol; Panisson, Josiane C; Agyekum, Atta K; Predicala, Bernardo Z; Alvarado, Alvin C; Agnew, Joy M; Sprenger, Charley J; Beaulieu, A Denise
Abstract: The objective of this project was to determine the impact of feeding growing pigs with high wheat millrun diets supplemented with a multi-carbohydrase enzyme (amylase, cellulase, glucanase, xylanase, and invertase activities) on nutrient digestibility, growth performance, and greenhouse gas (GHG ) output (carbon dioxide, CO2 ; nitrous oxide, N2 O; methane, CH4 ). Three experiments were conducted utilizing six treatments arranged as a 3 × 2 factorial (0%, 15%, or 30% wheat millrun; with or without enzyme) for the digestibility experiment or as a 2 × 2 factorial (0% or 30% wheat millrun; with or without enzyme) for the performance and GHG experiments. The digestibility, performance, and GHG experiments utilized 48 individually housed pigs, 180 pigs housed 5 per pen, or 96 pigs housed 6 per chamber, respectively. Increasing wheat millrun up to 30% in the diet of growing pigs resulted in decreased energy, nitrogen (N) and phosphorus (P) apparent total tract digestibility and net energy content ( P < 0.01). Overall, average daily gain (ADG ) and gain to feed ratio were reduced in pigs fed wheat millrun ( P < 0.05). Enzyme supplementation had minimal effects on the digestibility or performance parameters measured. Feeding diets with 30% millrun did not affect GHG output (CH4 : 4.7 and 4.9; N2 O: 0.45 and 0.42; CO2 : 1, 610 and 1, 711 mg/s without or with millrun inclusion, respectively; P > 0.78). Enzyme supplementation had no effect on GHG emissions (CH4 : 4.5 and 5.1; N2 O: 0.46 and 0.42; CO2 : 1, 808 and 1, 513 mg/s without or with enzymes, respectively; P > 0.51). Overall, the carbohydrase enzyme had minimal effects on parameters measured, regardless of wheat millrun inclusion ( P > 0.10). Although energy, N and P digestibility, and ADG were reduced, the inclusion of up to 30% wheat millrun in the diet has no effect on GHG emissions from growing pigs ( P > 0.10).